Ecological Concrete on Base Concrete-Building Waste - qizi, Boboqulova Shaxzoda Ravshan; Aziza, Kuldasheva (European Journal of Life Safety and Stability (2660-9630), 2022)
In this research the authors present the possibility to utilize some concrete building waste materials to produce ordinary ecological concrete (OEC) and improve the quality of concrete constructions. Recycled Concrete Aggregate (RCA) of 5-20 mm fraction were used and prepared the mixes,. Concretes with RCA were mixed with 265, 285 and 305 kg/m2 of three types of cements. The concrete sample specimens were tested for mechanical properties which are related to durability. After 28 days compressive strength increase to 43 MPa and after 90 days 59 MPa were achieved.